Impelementasi Media Daring Dalam Mendukung Pembelajaran di Masa Pendemi - Ubaidillah Kamal Faseh; Septi Gumiandari (Journal Of Dehasen Educational Review, 2020)
The Covid-19 pandemic has caused many activities to stop, including activities teaching and learning conventionally. Until a solver or deep solution is needed respond to these problems. Teaching and learning activities carried out online is a way to overcome that problem. Destination The research was to determine the use of online learning e-learning media for students at a university in Indramayu. The research instrument carried out on the collection of information and data is by means of questionnaires and library research. As a result of this research shows that online learning has been implemented well, and takes advantage of various learning media such as WhatsApp, Google Classroom, Zoom and Google Meet so learning becomes more varied and makes students not bored quickly and understand faster material delivered. There are several obstacles faced in implementation of online teaching and learning activities, namely the internet network that is not stable, lacking maximum availability of physical references and minimum data quota Internet. Online learning needs to be used as best as possible in activities learning and teaching because it is an innovation in learning so that students and lecturers can conduct lectures efficiently and effectively.